High Incidence of Different Drug Uses and Media Campaign on the Injection Method in Borno State, Nigeria - Ojemeiri Karl Airaoje; Eric Msughter Aondover; Aruaye Afeye Obada; Omolara Oluwabusayo Akin-Odukoya; Muhammad Ridwan (Budapest International Research and Critics University, 2024)
Injection drug abuse has become a major public health problem, the prevalence of which has increased significantly in the last decade. There are approximately 15.6 million people who inject drugs (PWID) worldwide and this may be an underestimate of the real problem as the use of injection drugs is an illegal and stigmatized practice, making data collection challenging. The study employed a cross-sectional design to assess drug abuse via injection and primary data was collected through structured interviews and self-administered questionnaires. Quantitative data were analyzed using Statistical Package for Social Science, employing descriptive statistics to identify patterns and associations while the qualitative data were transcribed and analyzed thematically to understand underlying behaviors and motivations. The cognitive-affective-pharmacogenic control theory was employed. Based on the findings, most of the respondents inject drugs because it provides a stronger high compare to other methods. The findings revealed that vein damage is the most common effect found among the people of high incidence of different drug uses through the injection method in Maiduguri Local Government Area of Borno State. Similarly, most of the respondents inject synthetic opioids and morphine. Also, most of the drug users are not receiving any support or treatment for drug addiction. The study concludes that most of the respondents are facing the problem of stigma and discrimination. Based on the findings, the study recommends that there should be educational outreach focused on sensitising and educating young people about the risks of drug use and promotes life skills through schools and community initiatives.